(untitled) (UNED Research Journal, 2021)
Introduction: La Amistad-Pacífico Conservation Area has includes three biological corridors that can benefit from native tree nurseries for reforestation and landscape permeabilization. Objective: To test a network of cost-effective community nurseries supported by local stakeholders to ensure long-term viability and evidence-based restoration. Methods: We stablished a reference nursery (>10 000 seedlings) and four small-scale ones (between 163 and 1 600 seedlings). We collected seedlings of 40 tree species between October 2020 and June 2021 and nursed them at an appropriate elevation, estimating survival for species with n ≥ 10. Results: The mean survival was 82%, with 16 species having a survival ≥ 80%. Seedlings with cotyledons did better. Reasons to establish nurseries include attraction of bees, aesthetics, shade, timber, food for wildlife and reforestation. Conclusion: These small-scale nurseries are viable and help communities to stay motivated and to estimate species survival.